Cortical reorganization of the glutamate synapse in the activity‐based anorexia rat model: Impact on cognition. Issue 4 (25th March 2022) - Mottarlini, Francesca; Targa, Giorgia; Bottan, Giorgia; Tarenzi, Benedetta; Fumagalli, Fabio; Caffino, Lucia
Abstract: Patients suffering from anorexia nervosa (AN) display altered neural activity, morphological, and functional connectivity in the fronto‐striatal circuit. In addition, hypoglutamatergic transmission and aberrant excitability of the medial prefrontal cortex (mPFC) observed in AN patients might underpin cognitive deficits that fuel the vicious cycle of dieting behavior. To provide a molecular mechanism, we employed the activity‐based anorexia (ABA) rat model, which combines the two hallmarks of AN (i.e., caloric restriction and intense physical exercise), to evaluate structural remodeling together with alterations in the glutamatergic signaling in the mPFC and their impact on temporal memory, as measured by the temporal order object recognition (TOOR) test. Our data indicate that the combination of caloric restriction and intense physical exercise altered the homeostasis of the glutamate synapse and reduced spine density in the mPFC. These events, paralleled by an impairment in recency discrimination in the TOOR test, are associated with the ABA endophenotype. Of note, after a 7‐day recovery period, body weight was recovered and the mPFC structure normalized but ABA rats still exhibited reduced post‐synaptic stability of AMPA and NMDA glutamate receptors associated with cognitive dysfunction. Taken together, these data suggest that the combination of reduced food intake and hyperactivity affects the homeostasis of the excitatory synapse in the mPFC contributing to maintain the aberrant behaviors observed in AN patients. Our findings, by identifying novel potential targets of AN, may contribute to more effectively direct the therapeutic interventions to ameliorate, at least, the cognitive effects of this psychopathology. Abstract : The combination of caloric restriction and intense physical exercise, two hallmarks of anorexia nervosa (AN) modeled in the activity‐based anorexia rat model, dysregulated the molecular composition of the glutamatergic synapse and reshaped the structural organization of the dendritic spine in the medial prefrontal cortex of adolescent female rats. These events, which persist even when body weight is restored and are paralleled by an impairment in recency discrimination memory, may contribute to identify novel potential targets of AN to more effectively direct the therapeutic interventions.